Σ54-dependent regulome in Desulfovibrio vulgaris Hildenborough. (December 2015) - Kazakov, Alexey; Rajeev, Lara; Chen, Amy; Luning, Eric; Dubchak, Inna; Mukhopadhyay, Aindrila; Novichkov, Pavel
Abstract Background The σ54 subunit controls a unique class of promoters in bacteria. Such promoters, without exception, require enhancer binding proteins (EBPs) for transcription initiation.Desulfovibrio vulgaris Hildenborough, a model bacterium for sulfate reduction studies, has a high number of EBPs, more than most sequenced bacteria. The cellular processes regulated by many of these EBPs remain unknown. Results To characterize the σ54 -dependent regulome ofD. vulgaris Hildenborough, we identified EBP binding motifs and regulated genes by a combination of computational and experimental techniques. These predictions were supported by our reconstruction of σ54 -dependent promoters by comparative genomics. We reassessed and refined the results of earlier studies on regulation inD. vulgaris Hildenborough and consolidated them with our new findings. It allowed us to reconstruct the σ54 regulome inD. vulgaris Hildenborough. This regulome includes 36 regulons that consist of 201 coding genes and 4 non-coding RNAs, and is involved in nitrogen, carbon and energy metabolism, regulation, transmembrane transport and various extracellular functions. To the best of our knowledge, this is the first report of direct regulation of alanine dehydrogenase, pyruvate metabolism genes and type III secretion system by σ54 -dependent regulators. Conclusions The σ54 -dependent regulome is an important component of transcriptional regulatory network inD. vulgaris Hildenborough and related free-livingDeltaproteobacteria . Our study provides a representative collection of σ54 -dependent regulons that can be used for regulation prediction inDeltaproteobacteria and other taxa.